What are the characteristics of online campaigns of female candidates? An analysis based on the 2018 Brazilian elections - Quesada Tavares, Camilla (2019)
The aim of this paper is to investigate the characteristics of the campaign by women candidates for the 2018 elections on Facebook. Considering that women receive little incentive from parties to run for public office, digital social networks represent a way of balancing the campaign among actors, as in traditional spaces, such as radio and television, they tend to get less time than male candidates. Thus, we seek to understand which campaign strategies they use in Facebook fan pages, with particular focus on gender issues. To achieve the objectives, we analyzed the campaign of six candidates who have different trajectories in politics. The research corpus consists of 1,958 posts made during the first round of the election campaign on Facebook fan pages, based on the quantitative content analysis methodology. The results indicate that the candidates have little gender discourse, and, when they do have it, it reinforces stereotypes.